Field Diagnosis of Citrus Tristeza Virus - Stephen H. Futch; Ronald H. Brlansky (EDIS)
Citrus tristeza virus (CTV) is one of the most important pathogens affecting citrus worldwide. Tristeza was first reported in Florida in the 1950s. By the 1980s, it produced serious losses due to tree decline and death on sour orange and Citrus macrophylla rootstocks. Tree decline continues to be a problem today in groves that still have sour orange rootstock trees remaining. Due to CTV, few if any nursery trees are being propagated in Florida on sour orange, bittersweet or Citrus macrophylla rootstock. This document is HS996, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2005.